The Interactive of E-Learning Unit to employ The Students Skills in Cyber Security According to Determinates of Digital Citizenship - Ghadeer Almehmadi (Umm Al-Qura University, 2023)
The study aimed to design an interactive of e-learning unit to employ students' skills in cyber security according to determinants of digital citizenship then measuring its effectiveness. The study relies on the descriptive approach and the quasi-experimental approach. To achieve study objectives, measurement tools were developed, namely cognitive test and observation card to measure the cognitive and performance aspects of cyber security skills according of the nine determinants of digital citizenship, which were applied in the second semester of the academic year (1443 AH / 2022 AD); On a sample of (33) undergraduate students at Umm Al-Qura University. Study results showed that there are statistically significant differences at α ≤ 0.05 among average score of the study sample in the pre and post application of the cognitive test of cyber security skills as a total score, and as sub-domains: (Education Field, Respect Field, and Protection Field) and as sub-dimensions of digital citizenship. So, all differences were in favor of post-application. The study also showed that there are statistically significant differences at α ≤ 0.05 among average score of the study sample in the pre and post application of the observation card of the performance aspect of cyber security skills as a total score, and as sub-domains: (Education Field, Respect Field, & Protection Field), and as sub-dimensions of digital citizenship. So, all differences were in favor of the post- application. The results also showed that the interactive e-learning unit has an impact on the development of the cognitive and performance aspects. and it was found that there is a positive correlation with statistical significance at α ≤ 0.05 between the cognitive side and the performance side of cyber security skills, after applying the program based on the interactive e-learning unit.